2016
DOI: 10.3892/etm.2016.3536
|View full text |Cite
|
Sign up to set email alerts
|

Separation of cordycepin from Cordyceps militaris fermentation supernatant using preparative HPLC and evaluation of its antibacterial activity as an NAD+-dependent DNA ligase inhibitor

Abstract: Abstract. Cordycepin exhibits various bio-activities, including anticancer, antibacterial, antiviral and immune regulation activities, and is a significant focus of research. However, the preparation of high-purity cordycepin remains challenging. Also, the molecular target with which cordycepin interacts to cause an antibacterial effect remains unknown. In the present study, cordycepin was prepared by preparative high-performance liquid chromatography (prep-HPLC) and the purity obtained was 99.6%, indicating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…By preventing excessive glutamateinduced oxidation and endoplasmic reticulum stress-associated apoptosis in hippocampal cells (Jin et al, 2014), it was also proved to have antioxidant effects (Kim et al, 2006). Besides, cordycepin was proved to have broad-spectrum antibiotic activity by inhibiting NAD + -dependent DNA ligase (Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…By preventing excessive glutamateinduced oxidation and endoplasmic reticulum stress-associated apoptosis in hippocampal cells (Jin et al, 2014), it was also proved to have antioxidant effects (Kim et al, 2006). Besides, cordycepin was proved to have broad-spectrum antibiotic activity by inhibiting NAD + -dependent DNA ligase (Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The only significant synergistic antibacterial effect was produced by combination of Cor and Gen at 50 µmol/L, which resulted in much higher antibacterial effect than when the compounds were used singly. It has been previously reported that Cor is an NAD + -dependent DNA ligase inhibitor which inhibits bacterial growth [24], whereas Gen inhibits DNA and protein synthesis in Klebsiella pneumonia [25]. Therefore, Cor and Gen may mediate their antibacterial activities through different mechanisms, which manifested in a synergistic inhibitory effect on E.coli growth.…”
Section: Discussionmentioning
confidence: 99%
“…Cordycepin, 3-deoxyadenosine, is a derivative of the nucleoside adenosine, and it is abundantly present in Cordyceps species (Ju et al 2009;Zhou et al 2016). Since cordycepin shows chemical similarity to adenosine, it could be involved in the incorporation of RNA molecule causing a broad range of biological activities (Chen et al 2017).…”
Section: Open Accessmentioning
confidence: 99%